Cardiovascular health in Italy. Ten-year surveillance of cardiovascular diseases and risk factors: Osservatorio Epidemiologico Cardiovascolare/Health Examination Survey 1998–2012. (29th August 2020) - Giampaoli, Simona; Palmieri, Luigi; Donfrancesco, Chiara; Noce, Cinzia Lo; Pilotto, Lorenza; Vanuzzo, Diego
Abstract: Background: Surveillance of and monitoring trends for cardiovascular diseases and risk factors are relevant when we consider that these diseases and conditions are largely preventable. The aim of this paper is to assess time trends of cardiovascular diseases, lifestyles, risk factors and high risk conditions in different socioeconomic levels. Methods: Paired but independent population samples of men and women aged 35–74 years located in all 20 Italian regions were examined in 1998–2002 ( n = 9612) and in 2008–2012 ( n = 8141). Time trends of lifestyles, cardiovascular risk factors, prevalence of high-risk conditions and cardiovascular diseases are shown for two different socioeconomic levels, as assessed by educational level. Results: Over 10 years, in both genders and socioeconomic classes, the prevalence of smoking decreased (from 32% to 23% in men) as well as mean levels of blood pressure (systolic from 136 mmHg to 133 mmHg in men and from 132 mmHg to 127 mmHg in women), while the prevalence of dyslipidemia and obesity increased reaching 35% and 25% of the population respectively; the prevalence of myocardial infarction remained stable (1.6% in men; about 0.5% in women), that of stroke decreased in men (from 1.2% to 0.7%); the prevalence of diabetes did not change (12% in men; 8% in women). In the low educational class, cardiovascular risk factors and diseases remained unfavourable compared with the high educational class. Conclusions: The burden of cardiovascular diseases and their risk factors remain high and require continuous appropriate action at the community and individual levels, as suggested by the European Guidelines for Cardiovascular Prevention.